Qualitative analysis of the Meals, Mindfulness, & Moving Forward (M3) lifestyle programme: Cultivating a 'safe space' to start on a 'new path' for youth with early episode psychosis. Issue 1 (12th January 2020) - Thompson, Andie; Senders, Angela; Seibel, Celeste; Usher, Craigan; Borgatti, Alena; Bodden, Katheryn; Calabrese, Carlo; Hagen, Kirsten; David, Jason; Bourdette, Dennis; Shinto, Lynne
Abstract: Aim: The Meals, Mindfulness, & Moving Forward (M 3 ) programme included nutrition education, hands‐on cooking classes, mindfulness meditation practice, physical activities and facilitated group sharing. M 3 was designed as a supplement to standard care for youths (age 15‐25 years) with first‐episode psychosis (FEP) who were clients of coordinated specialty care teams. M 3 's primary aim was feasibility by demonstrating high programme attendance; secondary aims included cardiometabolic measures. Data collection included quantitative and qualitative outcomes. The aim of the qualitative study was to understand participants' and study partners' experiences during the programme and to understand programme elements that were helpful for young people to sustain healthy lifestyle choices 6 weeks post‐programme. Methods: During the last programme session, we conducted two focus groups, one with participants (n = 13) and one with their study partners (n = 11); 6 weeks post‐intervention, individual semi‐structured interviews were conducted with 11 participants. All interviews were audio recorded and transcribed; grounded theory methods guided thematic analysis. Results: Main themes from the focus groups included appreciation for a 'non‐stigmatizing' environment providing participants and study partners with a sense of 'dignity' that enabled a 'new path'. Six weeks post‐intervention, participants reported continued use of mindfulness practice to stay grounded and assist with making healthful lifestyle changes. However, many were unsure of how to sustain these changes long‐term. Conclusion: The results suggest that young people with FEP value a non‐stigmatizing space that allows for social engagement and facilitates healthy behaviours. Short‐term, M 3 participants reported behaviour change but wanted on‐going support to sustain healthy behaviours.